Tuning unemployment insurance to the business cycle - Torben M. Andersen (IZA World of Labor, 2014)
High unemployment and its social and economic consequences have lent urgency to the question of how to improve unemployment insurance in bad times without jeopardizing incentives to work or public finances in the medium term. A possible solution is a rule-based system that improves the generosity of unemployment insurance (replacement rate, benefit duration, eligibility conditions) when unemployment is high and reduces the generosity when it is low.
Keywords: J6; H3; 330; unemployment benefits; insurance; incentives; automatic stabilizers